Patient and public involvement in neonatal research – experiences and insights from parents and researchers - Michella Bjerregaard; Ingrid Poulsen; Emma Carlsen; Antonio Esparza; Joanna Smith; Anne Brødsgaard (Research Involvement and Engagement)
Abstract Background Involving parents in decisions about the care of their infant is common practice in most neonatal intensive care units. However, involvement is less common in neonatal research and a gap appears to exist in understanding the process of patient and public involvement. The aim of this study was to explore parents and researchers’ experiences of patient and public involvement in a neonatal research project. Methods A qualitative design was employed, consisting of two focus group interviews, one dyadic interview, and four individual interviews with parents and researchers. The interviews followed a semi-structured guide specific to both parents and researchers. Data were analysed using content analysis as described by Graneheim and Lundman. Results A total of nine parents and four researchers participated in the study. Seven themes were consolidated into three core concepts: Embracing the ethos and pathos of patient and public involvement, Finding the path to maximise meaningful involvement, and Becoming skilled in engaging patients and the public in research. The core concepts highlighted both similarities and differences, as well as challenges and facilitators, of the experiences of the patient and public involvement process. Conclusion Patient and public involvement in research was a mutually beneficial process, facilitating learning and reflective opportunities for parents and researchers. However, there were challenges that emphasised the need for rapport building between parents and researchers, valuing everyone’s unique perspective and expertise, with clear communication and well-defined roles and goals. These insights offer a contribution for future patient and public involvement in health research.